2018
DOI: 10.1039/c7nr07154j
|View full text |Cite
|
Sign up to set email alerts
|

Complete amplitude and phase control of light using broadband holographic metasurfaces

Abstract: Reconstruction of light profiles with amplitude and phase information, called holography, is an attractive optical technology with various significant applications such as three-dimensional imaging and optical data storage. Subwavelength spatial control of both amplitude and phase of light is an essential requirement for an ideal hologram. However, traditional holographic devices suffer from their restricted capabilities of incomplete modulation in both amplitude and phase of visible light; this results in sac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
226
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 336 publications
(246 citation statements)
references
References 50 publications
(70 reference statements)
0
226
0
1
Order By: Relevance
“…This full and broadband complex‐amplitude modulation successfully provides vivid complex‐amplitude modulated holograms without any noise in the entire visible region, as shown in Figure E. Compared to the phase‐only holograms, this hologram achieves a signal‐to‐noise ratio (SNR) of 211, which is much higher than the SNR of 50 for phase‐only metasurface holography . Another advantage of complete complex‐amplitude modulation is elimination of the limited zone in designing computer generated holograms.…”
Section: Metasurface Holographymentioning
confidence: 91%
See 1 more Smart Citation
“…This full and broadband complex‐amplitude modulation successfully provides vivid complex‐amplitude modulated holograms without any noise in the entire visible region, as shown in Figure E. Compared to the phase‐only holograms, this hologram achieves a signal‐to‐noise ratio (SNR) of 211, which is much higher than the SNR of 50 for phase‐only metasurface holography . Another advantage of complete complex‐amplitude modulation is elimination of the limited zone in designing computer generated holograms.…”
Section: Metasurface Holographymentioning
confidence: 91%
“…This means that some distances from the wavefront plane (ie, the metasurface plane) should be provided, as the allowed space for holography is limited. However, complex‐amplitude modulation enables the holography to transcend the Fraunhofer condition so that even images can be reconstructed just above the metasurface plane, as shown in “S” images represented in Figure E .…”
Section: Metasurface Holographymentioning
confidence: 99%
“…This method is made possible by using a new structure, controlling the properties of incident light, or using a reflection space as modulating range with transmission space [21,[52][53][54][55][56][57][58][59]. The phase control via PB phase is well known to have a broadband characteristic [21,29,51]. However, if the resonant characteristic is added to the meta-atom for addition of auxiliary functionality or subsidiary information, the broadband operation becomes impossible [19,52,54].…”
Section: Metasurface Holography With More-than-one Informationmentioning
confidence: 99%
“…Notably, light manipulation through meta-atom has surpassed the conventional optic components in terms of their compactness as well as their performances [8,17]. Mostly, this nature has been utilized in abrupt phase discontinuities, generation of desired surface wave, sweeping polarization states with intensity, and creation of desired dispersive properties [18][19][20][21][22][23][24][25][26][27][28]. The metasurfaces first were exploited a lot for the desired wavefront control for the substitution of optic components with high-performance and ultrathin counterparts, such as hologram generation, lensing, and beam router [6,[29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…

the generation of Airy beams, it is highly desirable to locally control the amplitude and phase of the output beam simultaneously so as to satisfy the polynary amplitude and binary phase distributions. [15][16][17] Inspired by the flexibility of introducing complex field distributions, [18] various Airy beam generators, either for free-space light, [19][20][21][22][23][24][25] or surface plasmons, [20,[26][27][28][29][30] have been proposed and demonstrated based on metasurfaces. Recent studies have demonstrated that, manipulating the amplitude and phase simultaneously and independently leads to new wavefront manipulation effects and applications.

…”
mentioning
confidence: 99%